Publisher's Note. Celebrating Earth. - Hennessy Jr, Mike (Psychiatric Times, 2024)
An introduction is presented in which the editor discusses various reports within the issue on topics including the intersect of environmental factors and psychiatric disorders, suicide prevalence, and Black youth mental health improvement.